Rational Creatures and Free Citizens: The Language of Politics in the Eighteenth‑Century Debate on Women - Brown, Susan (Historical Papers / Communications historiques, 1988)
AbstractThis paper examines the intersection between the debate on women and the widerpolitical debates of late eighteenth-century England. During this period the meaning ofconcepts such as liberty, equality, and rights was contested not only with regard topolitical relationships among men, but also as they applied to civil and domesticrelationships between men and women. The language of politics encouraged thedefinition of women's oppression in terms of the unrepresentative nature of authorityexercised by men. The values of rationality, equality, and independence espoused byradicals in the debate on women were part of a larger conception of virtue, which carriedwith it political as well as moral implications. These political implications came to thefore in the conservative response. Conservatives' ideas on women were part of a largervision of social and political order in which duty, obedience, and dependence operated asthe unifying principles. Within this framework, radical proposals for a more egalitarianfamily structure were viewed as a potential threat to political order. At the heart of thisdebate lay not only a dispute regarding the condition of women, but also a strugglebetween two conflicting visions of the ideal society.